The experience of becoming a mother, being a woman with physical disabilities, in a wheelchair, in the Unified Health System (Research, Society and Development, 2024)
Based on the social model of disability, it is possible to conceive that the experience of exclusion and inequality experienced by people with disabilities arises from the interaction of an injured body and a non-inclusive society, such a model brings disability closer to a Human Rights issue, which includes the right to access health, recommended in Brazil by the Unified Health System (SUS). With this in mind, the research sought to report the experience of a woman with physical disabilities, in a wheelchair, who lived the experience of becoming a mother being assisted by SUS services, through a case study in a Municipal Public Hospital and Maternity, a reference for women's health, Baby-Friendly Hospital and Teaching Hospital in the north of São Paulo, through semi-directed interviews, using the phenomenological method, which aims to get closer to the meaning of the experience for the subject. The most relevant points brought up in the speech were reported. It was noted that all the health services by which the interviewee was assisted during pregnancy, childbirth and puerperium were not fully prepared to receive a woman with physical disabilities, in addition, it was seen that the interviewee still has difficulties in recognizing her rights as a person with disabilities and that there was an identification between the interviewee and the interviewer who is also a woman with a physical disability.